Obese patients have higher risk of breast cancer-related lymphedema than overweight patients after breast cancer: a meta-analysis - Wu, Ruxing; Huang, Xiaoyuan; Dong, Xiyuan; Zhang, Hanwang; Zhuang, Liang (Annals of Translational Medicine, 2019)
Background: Increasing scientific evidences suggest that body weight is a risk factor for breast cancer-related lymphedema (LE) in breast cancer patients, but many existing studies have yielded inconclusive results. This meta-analysis aims to provide a more precise estimation of the effects of body mass index (BMI) on LE in breast cancer patients. Methods: Two authors searched independently in the main English-language databases, including PubMed, Embase, and Cochrane Central Register of Controlled Trials, and the main Chinese databases, including China National Knowledge Infrastructure and WanFang Data from inception through June 1, 2018 in human. Odds ratios with 95% confidence interval were calculated to evaluate the effect of BMI on LE. Results: Twelve studies were identified with a total of 8,039 breast cancer patients, including 2102 patients who were suffered from LE; therefore, the total incidence of LE was 26.15%.The meta-analysis results reveal that the odds ratios were 1.42 [95% confidence interval (CI), 1.20 to 1.68] for BMI 25–30 kg/m2 versus BMI